"A machine masquerading as a movement": The 2015 UK general election labour campaign investigated through assemblage and affect. (April 2019) - Page, Sam
Abstract: This paper explores the election strategy of a local Labour Party campaign for the UK May 7 2015 General Election. Using data gathered through an ethnography, and conceptualising the party, local campaign and election through concepts of assemblage and affect (Deleuze and Guattari 2013), I look at the relationships, connections and materials (campaign literature, as well as digital tools such as Contact Creator) that constructed the local party campaign assemblage. Following assemblage theory, I examine the effects of the campaigns door-step method within the party. I argue that an election is imbued with different intensities, understandings and results that ask not only those political actors to perform the party and State in particular ways, but also the voting population to be part of that performance. As such, I show the always-changing (always becoming) relationship between 'society' and political parties by witnessing, participating in and questioning how lines appear between a Labour canvassing campaign assemblage and the society it is canvassing.